Seroprevalence, molecular detection, risk factor analysis and public health perceptions of brucellosis in donkeys across different production systems in Kenya - Kithuka, James Mutiiria; Wachira, Timothy Muthui; Onono, Joshua Orungo (Frontiers in Tropical Diseases, 2025)
IntroductionDonkeys are vital to livelihoods in Kenya, yet their exclusion from national disease surveillance leaves potential health risks underexplored. Brucellosis, a significant zoonosis, remains poorly characterized in donkeys despite frequent close contact with humans. This study aimed to determine the seroprevalence, molecular detection, and risk factors for Brucella spp. infection in donkeys, and to assess owner knowledge, attitudes, and practices (KAP) across seven Kenyan counties representing diverse production systems.MethodsBetween October 2024 and February 2025, a cross-sectional survey sampled 392 donkeys. Serum was tested using the Rose Bengal Plate Test (RBPT) and indirect ELISA (iELISA). Donkeys testing seropositive on either test (n = 42) had their corresponding whole blood samples subjected to DNA extraction for PCR analysis, targeting Brucella abortus and Brucella melitensis. Structured interviews with owners were conducted to assess knowledge, attitudes, and practices (KAP). Mixed-effects logistic regression in R was used to identify risk factors.ResultsOverall seroprevalence was 10.7% by RBPT, 2.0% by iELISA, and 0.0% by PCR. All iELISA-positive cases (n = 8) were from Turkana (4), Narok (3), and Nairobi (1). Young donkeys (<3 years) had significantly higher odds of being seropositive (aOR = 11.8; 95% CI: 1.70–81.99; p = 0.013). Owner knowledge was low—only 25.3% had heard of brucellosis and risky practices were common, with 91.1% assisting foaling without protective equipment and 19.4% consuming donkey products, often raw.ConclusionDonkeys in Kenya may contribute to Brucella transmission within mixed livestock systems and to humans. Inclusion of donkeys in brucellosis surveillance, targeted community education, and improved diagnostics are recommended. These findings provide the first field-based evidence of donkey brucellosis in Kenya and underscore the importance of integrating donkeys into One Health strategies to reduce zoonotic risk.